The Core Vocabulary of Romance Plurilingualism : French and Italian word lists - Meißner, Franz-Joseph; Justus Liebig University Giessen (My University, 2021)
The two volumes unite all the lemmas of the Core Vocabulary of Romance Plurilingualism. The CVRP is a 28,000-entry electronic list of French, Italian, Portuguese and Spanish words with a frequency rank below 5000 and their German and English equivalents. The free of charge learning app EuroComDidact ToGo, fed by the CVRP inventory, arranges its inventory into 9550 series of semantic equivalents. They combine the user s already existing lexical knowledge with the vocabulary to be learned by simply comparing corresponding forms. According to the learners needs, it is also possible to selectively organize the inventory by frequency intervals, bridging and target languages combinations or interlingual transparency classes. Thus, the CVRP is a powerful tool for learning and maintaining Romance plurilingualism and for analysing and composing learning materials from a lexico-didactic point of view as well. (For more information visit: https://eurocomdidact.eu)
Keywords: ddc:440